Dhea Use to Improve Likelihood of Ivf/Icsi Success in Patients with Diminished Ovarian Reserve: A Systematic Review and Meta-Analysis - Schwarze-Meza, J (Lippincott Williams and Wilkins, 2019)
Despite advances in in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI), poor ovarian response (POR) remains a challenging issue. The frequency of POR is estimated to occur in 5% to 18% of IVF/ICSI cycles and has a corresponding pregnancy rate of 2% to 4%. © 2019 Wolters Kluwer Health, Inc. All rights reserved.